Intrinsic Benefits of Presplitting - Relieving Gas Penetration in Addition to Lowering Blast Vibrations to Highwalls - Ruilin Yang; J. P. Remi Proulx; Areli Rodriguez (International Society of Explosives Engineers, 2025)
Historically, presplitting has been considered effective in reducing the impact of blast vibrations on highwalls. However, it remains a debated topic: how significantly can it protect highwalls, and is it worth the cost and effort to implement presplit blasting techniques? In hard rock, presplit blasting can leave half-barrels on the highwalls, clearly demonstrating its usefulness. However, in a fractured rock mass, the half-barrels from presplit blasting may not appear in most cases, leading to questions about its role in protecting highwalls. Previous studies in the literature used geophones to measure blast vibrations at far distances and could not ascertain the significant benefit of presplit blasting in reducing the impact of blast vibrations on highwalls. Additionally, no studies in the literature address the role of presplitting in alleviating blasting-released gas pressure that could penetrate joints and open new fractures in highwalls. Yang & Proulx (2019) and Yang et al. (2022) using near-field blast vibration monitoring of signature hole blasts have revealed that the peak particle velocity (PPV) of blast vibrations at a scaled distance of 1 m/kg^0.5 can be reduced by 50% or more for presplit-filtered vibrations. These results have been confirmed for both hard rock and fractured ground. In addition to summarizing the reduction in blast vibrations due to presplitting for both hard rock and a fractured rock mass, this paper demonstrates the relief of subsequent blasting gases after the detonation of blastholes. This is shown through video recordings of gas ejections from a row of empty previously fired presplit blastholes located 6 to 9 meters away from the detonation edge or final buffer row of a blasthole pattern. The results clearly show that presplitting not only lowers blast vibration PPV’s but also reduces the entry of the gases produced by the detonation process into rock fractures and or open joints.